Immunoscreening of Plasmodium falciparum proteins expressed in a wheat germ cell-free system reveals a novel malaria vaccine candidate - Morita, Masayuki (Sci Rep, 2017)
The number of malaria vaccine candidates in preclinical and clinical development is limited. To identify novel blood-stage malaria vaccine candidates, we constructed a library of 1,827P. falciparum proteins prepared using the wheat germ cell-free system (WGCFS). Also, a high-throughput AlphaScreen procedure was developed to measure antibody reactivity to the recombinant products. Purified IgGs from residents in malaria endemic areas have shown functional activity against blood-stage parasites as judged by an in vitro parasite Growth Inhibition Assay (GIA). Therefore, we evaluated the GIA activity of 51 plasma samples prepared from Malian adults living in a malaria endemic area against the WGCFS library. Using the AlphaScreen-based immunoreactivity measurements, antibody reactivity against 3 proteins was positively associated with GIA activity. Since anti-LSA3-C responses showed the strongest correlation with GIA activity, this protein was investigated further. Anti-LSA3-C-specific antibody purified from Malian adult plasmas showed GIA activity, and expression of LSA3 in blood-stage parasites was confirmed by western blotting. Taken together, we identified LSA3 as a novel blood-stage vaccine candidate, and we propose that this system will be useful for future vaccine candidate discovery.